Malleable and recyclable imide–imine hybrid thermosets: influence of imide structure on material property. Issue 13 (1st June 2021) - Shen, Xiran; Ma, Yunlong; Luo, Shichang; Tao, Rao; An, Dan; Wei, Xinlei; Jin, Yinghua; Qiu, Li; Zhang, Wei
Abstract : Novel hybrid material poly(imide-imine) has been prepared, which exhibits self-healing behavior and recyclability enabled by the dynamic imine bonds while retaining the tunable and excellent mechanical and thermal properties of polyimide. Abstract : Although thermosetting polyimides have been widely used in many fields, it is still a challenging task to realize their repairability, reprocessibility, and recyclability, which are highly desirable in mitigating the cost and environmental concern. In this work, a series of malleable imide–imine hybrid thermosets were prepared through imine condensation of amino-terminated imide macromonomers with a dialdehyde and triamine crosslinker. Such novel hybrid materials exhibit rehealability and recyclability enabled by the dynamic imine bonds, while retaining the excellent mechanical and thermal properties of polyimide. Success here not only expands the library of building blocks for preparation of repairable and recyclable polyimides targeting different applications, but also opens new possibilities for reprocessing thermosetting polymers and developing high-performance dynamic covalent hybrid polymeric materials.